I2M3-Based Interactive Multimedia Traces of Culture: An Innovative Approach to Learning Indonesian Cultural Diversity in Elementary Schools - I Gusti Agung Ratih Puspaningrat; I Gusti Agung Ayu, Wulandari; Didith Pramunditya , Ambara (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes of elementary students in the topic of Indonesian Cultural Diversity are caused by the lack of innovative, interactive, and contextual learning media. This condition results in limited student engagement and inadequate conceptual understanding. This study aims to develop and evaluate the effectiveness of the Jejak Budi interactive multimedia based on the I2M3 model in enhancing students’ learning outcomes on Indonesian Cultural Diversity. This research employed a development research design using the ADDIE model. The research subjects consisted of one content expert, one instructional design expert, one media expert, three students for individual trials, nine students for small group trials, and 23 students for the effectiveness test. Data were collected using questionnaires and multiple-choice objective tests, and analyzed through descriptive quantitative analysis and inferential statistics using a one-sample t-test. The results showed that the Jejak Budi interactive multimedia based on the I2M3 model was highly feasible, with expert and user trial feasibility percentages ranging from 90.79% to 95%. Hypothesis testing revealed a significance value of 0.000 < 0.05, indicating that the multimedia is effective in improving student learning outcomes. This research implies that adaptive and effective interactive multimedia innovations can significantly support learning in elementary schools.